Mature Embryo-Based in vitro Regeneration of Indica Rice Cultivars for High Frequency Plantlets Production - Barman, HN; Hoque, ME; Roy, RK; Biswas, PL; Khan, MAI; Islam, MO (Bangladesh Rice Journal, 2017)
The study was conducted at Biotechnology Division of Bangladesh Rice Research Institute (BRRI) to investigate the effects of plant growing medium and plant growth regulator (PGR) for the callus induction and high frequency plantlets regeneration of indica rice. Ten indica rice varieties viz. BR5, BR11, BRRI dhan28, BRRI dhan29, BRRI dhan33, BRRI dhan41, BRRI dhan47, BRRI dhan48, BRRI dhan49 and BRRI dhan50 were cultured on MS, N6 and LS media. The MS medium was found better for callus induction as compared to N6 and LS media. Among the tested varieties BRRI dhan48 induced the highest percent and best quality callus. Interaction effects of BRRI dhan48 to MS medium yielded 71.55% callus induction. The regeneration efficiency of BRRI dhan48 was tested on MS medium supplemented with different combination of NAA plus BAP and NAA plus kinetin. MS medium supplemented with 2.0 mg L-1 NAA and 2.0 mg L-1 Kn was found the best in respect of percent regenerated (76.67%) plantlet as well as for the growth of plantlets in vitro. Bangladesh Rice j. 2016, 20(2): 81-87